Хвильові процеси в підвісі гіроскопа з довільним окресленням лінії меридіана поплавця - Мельник, В.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The theory of the elastic interaction of the suspension of a gyroscope with an external wave perturbation under an arbitrary geometry of the meridian line form is constructed. The ways to compensate this influence with passive methods are presented.